Highly regio- and enantioselective multiple oxy- and amino-functionalizations of alkenes by modular cascade biocatalysis - Shuke Wu (Nature Portfolio, 2016)
Biocatalysis can perform highly selective multi-step synthesis in one pot, but with a limited range of non-natural reactions and products. Here, the authors report regio- and enantioselective bio-cascades, able to convert styrenes into a number of nitrogen and oxygen containing chiral molecules.